Spatial ecology of cactus bugs: interactions among suitable habitat, connectivity, and movements - Schooley, Robert Lee, author; Wiens, John, advisor; Burnham, Kenneth, committee member; Steingraeber, Dave, committee member; Van Horne, Bea, committee member (Colorado State University. Libraries, 2002)
A key issue in spatial ecology and conservation biology is how individuals and populations respond to habitat patchiness. It is critical that we develop some guidelines regarding how much of the complexity of landscape structure and movement behavior must be considered to understand how animals live in fragmented landscapes. I address this and related topics with a system of cactus bugs (Chelinidea vittiger) and their host plant, Opuntia polyacantha, in the short-grass steppe of Colorado. Within two patchy landscapes that differed in matrix structure, I examined how landscape structure influenced the inter-patch movements and the distribution and abundance patterns of C. vittiger. Movement rates of adults were strongly affected by the nature of the matrix. Hence, dispersal is not a fixed value for C. vittiger; it depends on the resistance of matrix elements. Patch area set an upper constraint to the number of individuals within patches, and density was negatively related to patch area. Models of the occupancy and abundance of C. vittiger among patches that included a measure of patch connectivity that ignored matrix structure performed well for a landscape with a fairly homogeneous matrix. A more complex model that adjusted connectivity based on matrix structure was needed to explain patterns on a landscape with a heterogeneous matrix. Experimental releases of individuals within the matrix demonstrated that the ability of C. vittiger to detect habitat patches depended on environmental conditions. In particular, their movement behavior and perceptual range was strongly influenced by wind direction. These results suggest that C. vittiger uses olfaction to find habitat patches. For some species, perceptual range may be anisotropic and patch connectivity may be temporally dynamic and directional. We need to broaden our view of connectivity so that it explicitly considers the natural history of the focal species. Developing useful generalizations about the degree of complexity that must be incorporated when investigating patchy systems should be possible, but only after a more complete empirical foundation is established of how different species respond to environmental heterogeneity.
Keywords: ecology; entomology